Improved salt iodation methods for small-scale salt producers in low-resource settings in Tanzania - Assey Vincent D; Tylleskär Thorkild; Momburi Philip B; Maganga Michael; Mlingi Nicholaus V; Reilly Marie; Greiner Ted; Peterson Stefan (BMC, 2009)
Abstract Background Universal salt iodation will prevent iodine deficiency disorders (IDD). Globally, salt-iodation technologies mostly target large and medium-scale salt-producers. Since most producers in low-income countries are small-scale, we examined and improved the performance of hand and knapsack-sprayers used locally in Tanzania. Methods We studied three salt facilities on the Bagamoyo coast, investigating procedures for preparing potassium-iodate solution, salt spraying and mixing. Different concentrations of solution were prepared and tested using different iodation methods, with the aim of attaining correct and homogeneous iodine levels under real-life conditions. Levels achieved by manual mixing were compared to those achieved by machine mixing. Results The overall median iodation level in samples of salt iodated using previously existing methods was 10.6 ppm (range 1.1 - 110.0 ppm), with much higher levels in the top than the bottom layers of the salt bags, p < 0.0001. Experimentation using knapsack-sprayers and manual mixing led to the reliable achievement of levels (60.9 ppm ± 7.4) that fell within the recommended range of 40 - 80 ppm. The improved methods yielded homogenous iodine concentrations in all layers of salt-bags (p = 0.58) with 96% of the samples (n = 45) falling within 40 - 80 ppm compared to only 9% (n = 45) before the experiment and training (p < 0.0001). For knapsack-spraying, a machine mixer improved the iodine levels and homogeneity slightly compared to manual mixing (p = 0.05). Conclusion Supervised, standardized salt iodation procedures adapted to local circumstances can yield homogeneous iodine levels within the required range, overcoming a major obstacle to universal salt iodation.